Processo de dobramento a frio de chapas finas metálicas: análises por elementos finitos, experimentos e uma proposta para a compensação do retorno elástico - Silva, Jonatan Augusto da (Universidade Federal de São Carlos, 2022)
Mechanical forming operations are developed in several applications in industrial environments and are divided into some different operations, including cutting, bending, forging. Among the various processes, the bending operation, although quite simple, presents a phenomenon that appears when the load is relieved, and this phenomenon is known as springback. The springback, which is also known as elastic material return, causes the material to partially return to its initial state that it presented before the bending process, which is a problem of great relevance in the industrial environment, which provides a gap research in order to minimize its impacts. The goal of this work is to propose alternatives to predict the elastic behavior of aluminum sheets when undergoing the bending process, suggesting possible changes during the process, such as the application of forces and adjustments to tools and molds. The applied methodology consists of experimentally studying the behavior of the springback during the application of folds in aluminum plates and comparing its results using numerical simulation resources with finite elements applying the Abaqus® software for the modeling and simulation of the process. A metallographic analysis must be performed before and another after the test to present the study of the microstructural variation in line with the springback behavior. Through the analysis of these, it is expected to be possible to propose significant changes in the process so that the negative effects of the emergence of springback are minimized, thus elaborating extended variations for a range of fold operations using the same materials. It was possible to conclude that the compensation proposal presented satisfactory results in the numerical and experimental analyzes using the solution proposed in the course of the work, which al inserting changes in the geometry of the matrices provided bending results close to the expected values.
Thin sheet metal cold bending process: finite element analysis, experiments and a proposal for the explanation of springback
Keywords: Retorno elástico; Elementos finitos; Dobramento de chapas; Springback; Finite elements; Sheet metal bending; ENGENHARIAS::ENGENHARIA MECANICA::MECANICA DOS SOLIDOS; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO